Pokhodyashinite, CuTlSb2(Sb1-xTlx)AsS7-x, a new thallium sulfosalt from the Vorontsovskoe gold deposit, Northern Urals, Russia - Kasatkin,A.V.; Plasil,J.; Makovicky,E.; Skoda,R.; Agakhanov,A.A.; Tsyganko,M.V. (Journal of Geosciences, 2022)
Pokhodyashinite CuTlSb2(Sb1-xTlx)AsS7-x, is a new sulfosalt from the Vorontsovskoe gold deposit, Sverdlovsk Oblast’, Northern Urals, Russia. It forms anhedral grains up to 0.1 × 0.05 mm in size in calcite and is associated with major orpiment, pyrite, realgar and minor baryte, clinochlore, As-bearing fluorapatite, harmotome, prehnite, native gold and a rich spectrum of sulfosalts. Pokhodyashinite is black, opaque, and has a metallic luster and a black streak. It is brittle, with an uneven fracture and poor cleavage on {010}. The Vickers hardness (VHN, 20 g load) is 55 kg/mm2, corresponding to a Mohs hardness of 2. The calculated density is 5.169 g/cm3. In reflected light, pokhodyashinite is grayish-white, bireflectance is distinct. In crossed polars, it is strongly anisotropic; rotation tints vary from dark brownish gray to light bluish-gray. No internal reflections are observed. The reflectance values for wavelengths recommended by the Commission on Ore Mineralogy of the IMA are (Rmin/Rmax, %): 28.9/34.6 (470 nm), 27.6/33.4 (546 nm), 26.7/32.4 (589 nm), 26.1/31.1 (650 nm). The empirical formula of pokhodyashinite based on ΣMe = 6 apfu is Cu0.700Ag0.340Tl1.320Pb0.020Sb2.630As0.990S6.625. Pokhodyashinite is monoclinic, space group C2/m, a = 23.431(5), b = 3.996(2), c = 14.070(3) Å, β = 110.23(3)°, V = 1236.1(8) Å3 and Z = 4. Its structure can be described as wavy slabs of a complex structure based on double-rods of Sb-coordination pyramids and lone-electron-pair interspaces/micelles, separated by wavy interlayers consisting of paired columns of Tl and rods of paired Cu-coordination polyhedra. A small amount of Tl-for-Sb substitution results in partial anion vacancies in one sulfur site. The new mineral is named in honor of Maxim Mikhailovitch Pokhodyashin, a pioneer of mining engineering and smelting works in the Northern Urals of the 18th century.
Keywords: pokhodyashinite; new mineral; copper; thallium; sulfosalt; crystal structure; Vorontsovskoe gold deposit; Northern Urals